Spatial-temporal dynamics of thermal pollution of the environment in Essentuki - E. A. Skripchinskaya; D. S. Tasenko; M. B. Kagan (Наука. Инновации. Технологии, 2024)
The object of the study is the urban landscapes of the city of Essentuki. The aim of the work is to study spatial-temporal dynamics of thermal pollution of the environment in Essentuki and identify the factors influencing this process. The key task of the study is to identify the dependence of changes in the temperature of the earth’s surface on the degree of residential development and landscape. Methods of remote sensing and geographic information systems have been applied. Satellite images of the Landsat 8 and Sentinel-2 satellites were used for the analysis. The work involves channels – infrared near and thermal (Landsat 8 satellite), as well as the visible range. The average, maximum and minimum values of surface temperature for microdistricts are calculated. For a comparative analysis, the coefficients of landscaping, urban planning load and free territory were applied. Data processing has been verified in the QGIS environment. The average, maximum and minimum values of surface temperature for microdistricts are calculated. The coefficients of landscaping, urban planning load and free territory are calculated. Based on the results of the work, the spatial features of the distribution of thermal anomalies associated with the active development of microdistricts of the city were established. Cartographic material on the temperature of the earth’s surface for 2014, 2018 and 2022 years has been created and the areas of built-up areas and green infrastructure have been calculated. Such studies provide a comprehensive assessment of such a phenomenon as “heat islands” and make a significant contribution to the study of the city’s climate and the impact of urbanization processes on the environment, allowing to control the microclimate of urban areas, identify the direction and dynamics of changes existing in the urban environment. When planning a city, it is necessary to take into account the results of the study in order to compensate for the impact of the urban heat island. The primary task is to transfer knowledge about the urban climate into the daily practice of urban planning and design.